ANALISIS KONTRIBUSI GENDER DALAM BUDIDAYA TANAMAN KUCAI SKALA RUMAH TANGGA DI LAHAN PEKARANGAN - Pintakami, Lintar Brillian (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2018)
The purpose of this study was to describe the participation of women farmers in the formation of Kampung Kucai through Kelompok Wanita Tani (KWT), as well as identifying gender roles and assessing the extent of women's contribution to household income through home gardening optimization for farming activities in Kampung Kucai. the location of the research is purposive in Kampung Kucai, Dusun Kranggan, Pojok Village, Blitar Regency. The study was conducted from March to April 2018. The sampling method used in this study was snowball sampling. The number of respondents in the study were 20 respondents, both husband and wife who were actively involved in Kelompok Wanita Tani (KWT) in Kampung Kucai. In addition there are 5 Key Informants. Data analysis used descriptive analysis using qualitative and quantitative approach. Based on the data analysis it can be seen that the participation of women in the formation of the village of kucai in the form of cultivation of kucai, promoting, until the sustainable management. The identification of gender roles in the management of cucumber farming in the yard is analyzed by differentiating roles / activities, differences of control (power) and access (opportunities), and benefits between men and women. Then for the time allocation of men in the role of production shows greater than women. Men allocate production roles for 10 hours / day or 66.7%. While women allocate production role for 5 hours / day or 33,3%. So that each contribution in household net income each month is Rp. 460,230, - for men and Rp. 229.770, - for women. While the allocation of female reproductive role is bigger than men with value respectively 50% and 14,5%.